Education Paradigm Shifts in the Age of AI: A Spatiotemporal Analysis of Learning - Ruojun Zhong (仲若君); Yong Zhao (赵勇) (ECNU Review of Education)
Purpose The purpose of this article is to analyze how to make changes to prescribed curriculum, pedagogy, activities, learning environments, and assessments to loosen control over time and space of learning to increase time for student autonomy. Design/Approach/Methods A theoretical analysis of functions of the five elements (curriculum, pedagogy, activities, learning environments, and assessments) of schooling in controlling time and space in learning. Findings Students’ time available for autonomy is limited due to prescribed curriculum, which occupies all students’ school time. Pedagogical practices that aim to efficiently implement the prescribed curriculum force and tempt students to spend all available time on the prescribed curriculum and extend work on the prescribed curriculum beyond classrooms through time concentration. Furthermore, the design and implementation of learning activities alter students’ perception of time, making activities long and tedious. Moreover, students’ time occupation by the prescribed curriculum compresses their space in learning environments. Finally, assessments and evaluations are typically limited to a distorted picture of students due to misplaced observers on different time scales and from an observation perspective. All these can be changed and we proposed possible directions of change. Originality/Value This article furthers our positions in the previous article published in ECNU Review of Education —“Paradigm Shifting in Education: An Ecological Analysis.” In this article, we provided a more detailed analysis of schooling from spatiotemporal perspectives and gave a uniquely fresh perspective on the changes we need in the age of AI to increase the time available for autonomy.